Bibliometric review on FDI attractiveness factors. (31st January 2022) - Bretas, Vanessa P.G.; Alon, Ilan; Paltrinieri, Andrea; Chawla, Kavilash
This article reviews the literature on foreign direct investment (FDI) attractiveness factors through bibliometric and content analyses. We analyse 499 articles between 1994 and 2021 extracted from the Web of Science database. Using Bibliometrix R-package and VOSviewer software, we combined co-citation, bibliographic coupling, and keyword co-occurrence temporal analysis with a content analysis of the most cited articles. Five main research categories are revealed: structure for FDI, market conditions, entry conditions, institutional framework, and resources offer. We propose a conceptual framework of FDI attractiveness factors aligned with FDI motives. The article comprehensively reviews the key determinants using quantitative and qualitative approaches and provides future research directions.